PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA CV. NONYDA MAKASSAR - Andi Marlinah; Nurmasitah Nurmasitah (AkMen JURNAL ILMIAH, 2020)
This study was aims to determine the effect of working caoital turnover and accounts receivable turnover on profitability ini CV. Nonyda Makassar. This study uses secondary data in the form of company monthly financial statements from 22016 – 2019 0r 36 months. The results of this study prove that partially working capital turnover has a positive and significant effect on profitability, while accounts receivable turnover does not significantly influence profitability. This study also proves that working capital turnover and receivables turnover simultaneously effect profitability. This study produces a coefficient of determination of 71,3% which shows that profitability is influenced by variable working capital turnover and account receivables turnover. While the remaining 28,7% showed that profitability was influenced by variables not examined in this study